2021
DOI: 10.1002/ags3.12519
|View full text |Cite
|
Sign up to set email alerts
|

Grip strength as a predictor of postoperative delirium in patients with colorectal cancers

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 33 publications
1
19
1
Order By: Relevance
“…21 Arita et al reported that the incidence of postoperative delirium was 13.3% in patients ≥70 years old who underwent colorectal cancer surgery. 25 This difference in the incidence of postoperative delirium between the present study and previous reports may be due to our setting the target age higher than in other studies, as we targeted patients ≥75 years old in our study. An older age is reported to be an extremely important risk factor for the development of postoperative delirium in predisposed patients.…”
Section: Ta B L E 3 a Comparison Of Preoperative Factors Between Pati...contrasting
confidence: 63%
See 2 more Smart Citations
“…21 Arita et al reported that the incidence of postoperative delirium was 13.3% in patients ≥70 years old who underwent colorectal cancer surgery. 25 This difference in the incidence of postoperative delirium between the present study and previous reports may be due to our setting the target age higher than in other studies, as we targeted patients ≥75 years old in our study. An older age is reported to be an extremely important risk factor for the development of postoperative delirium in predisposed patients.…”
Section: Ta B L E 3 a Comparison Of Preoperative Factors Between Pati...contrasting
confidence: 63%
“…To assess the cognitive function of patients, the MMSE and Hasegawa Dementia Scale‐Revised (HDS‐R) are widely used. An MMSE score <23 is reported as an independent preoperative predictive factor for postoperative delirium in older patients who undergo colorectal surgery (OR 3.50, 95% CI 1.36–9.02, p = 0.009), 25 and an HDS‐R score <20 is reported to be an independent preoperative predictive factor for postoperative delirium in elderly patients who undergo urological surgery (OR 3.50, 95% CI = 1.36–9.02, p = 0.009) 23 . Our study also showed an MMSE ≤24 to be an independent preoperative predictive factor for postoperative delirium, which is consistent with previous reports (Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to RCC, numerous studies have found that PBT has a significant adverse effect on cancer survival in several types of malignant solid tumors, such as gastric, colorectal, and bladder cancer. [ 12 , 31 , 32 ] To explain this phenomenon, several possible mechanisms have been proposed. First, these deleterious effects are thought to be associated with suppressive transfusion-related immunomodulation (TRIM) and proinflammatory effects mediated by apoptotic cells, residual leukocytes and modified biological response including soluble mediators, cytokines, and soluble HLA peptides.…”
Section: Discussionmentioning
confidence: 99%
“…In daily clinical practice, it is time- and manpower-consuming to assess the five aforementioned items. Conversely, hand grip strength can be measured simply and quickly, and some previous studies including surgical and non-surgical hospitalized patients showed that low hand grip strength was associated with the development of delirium [ 5 , 6 ]; however, these associations in patients undergoing cardiac surgery have been poorly documented.…”
Section: Introductionmentioning
confidence: 99%